TIPE DAN ESTIMASI TEMPERATUR AIR BAWAH PERMUKAAN DAERAH PANAS BUMI GUNUNG PAPANDAYAN, GARUT, JAWA BARAT - Fauzan Thaha Assegaf; Agus Didit Haryanto; Johanes Hutabarat; Dewi Gentana (PPSDM Geominerba, 2020)
The location of the Papandayan study area is administratively located in the Cisurupan District, Regency Garut, West Java Province, was chosen as a research site because estimated to be an area that has geothermal potential. The purpose of this study is to determine the direction of the alignment of the structure, type of fluid, origin, and approximate subsurface temperature of the geothermal fluid.The method used in this research is DEM-SRTM image to determine the pattern of ridge and valley alignment that reflects the geological structure in the study area. Data processing of geochemical laboratory analysis results of geothermal fluid and remote sensing are supported by observing the phenomenon of landscape, geological structure and physical properties of geothermal manifestations on the surface in the field. The results of the alignment analysis of the SRTM-DEM image processed in the rosset diagram shows the alignment pattern (geological structure) in the study area tend to have North East-South West. The results of water chemical data plotting in the Cl-SO4-HCO3, Cl-Li-B and Na-K-Mg ternary diagrams show the characteristics, types of water in the study area as chloride-sulfate and sulfate types. The fluids move to the surface as an upflow and have been mixed and diluted with shallow ground water or meteoric water, and significant reaction occurs between the fluid and the wall rock which it passes. The results of the calculation by using water geothermometer, it can be estimated that subsurface temperature in the study area between 170°C-237°C.